Preparation of soy protein hydrolysates with antioxidant activity by using peptidases from latex of Maclura pomifera fruits - Reyes Jara, Andrea Milagros (2018)
A partially purified proteolytic extract prepared from Maclura pomifera latex was employed in hydrolyzing a soybean-protein isolate (4.2 mg/mL). The hydrolysis-product formation, monitored by tricine–sodium-dodecyl-sulfate–polyacrylamyde-gel electrophoresis and reverse-phase high-performance liquid chromatography, indicated that after 10 min of reaction the main soybean proteins disappeared. The maximum degree of hydrolysis was 36.2% after a 180-min digestion. The 90-min hydrolysate presented an IC50 of 31.6 ± 0.2 µg/mL, and a trolox equivalent antioxidant capacity of 157.6 and 176.9 µmoles TE per g of peptide determined by two different methods. Analysis by matrix-assisted–laser-desorption-ionization–time-of-flight mass spectrometry (MALDI-TOF MS), followed by the application of bioinformatics tools, enabled the deduction of fourteen theoretical peptide sequences containing antioxidant amino acids at >60%, none of which sequences had been previously reported as antioxidants. Finally, we consider that this 90-min hydrolysate would constitute a promising ingredient in the manufacture of functional foods.